1974
DOI: 10.1128/jvi.14.4.934-944.1974
|View full text |Cite
|
Sign up to set email alerts
|

Replication of a Nuclear Polyhedrosis Virus in a Continuous Cell Culture of Spodoptera frugiperda: Purification, Assay of Infectivity, and Growth Characteristics of the Virus

Abstract: Nonoccluded virus, polyhedra, and occluded virus were purified from a continuous cell culture of Spodopera frugiperda infected with nuclear polyhedrosis virus. The optimal temperature for the replication and lateral transmission of infectivity for the nuclear polyhedrosis viruses (NPV) in cell culture was 27 C. End-point dilution and plaque assay procedures for the measurement of infectivity are described and compared. Dose-response data demonstrated that a single particle could initiate an infection, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
1

Year Published

1976
1976
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(35 citation statements)
references
References 16 publications
(13 reference statements)
2
32
0
1
Order By: Relevance
“…This experiment confirmed our previous hypothesis that infected cells live longer in an oxygen-limited (low agitation) environment, even longer than uninfected cells when in an oxygenlimited stationary phase (see Figures 1 and 2). Since cell division and cellular DNA synthesis are blocked in infected cells, cellular regulation becomes controlled by the viral DNA replication, transcription, and translation activities (Fraser, 1989;Knudson and Tinsley, 1974). Consequently, if viral-associated activity is attenuated by the lack of oxygen, the cells remain in a suspended or quiescent state.…”
Section: Resultsmentioning
confidence: 99%
“…This experiment confirmed our previous hypothesis that infected cells live longer in an oxygen-limited (low agitation) environment, even longer than uninfected cells when in an oxygenlimited stationary phase (see Figures 1 and 2). Since cell division and cellular DNA synthesis are blocked in infected cells, cellular regulation becomes controlled by the viral DNA replication, transcription, and translation activities (Fraser, 1989;Knudson and Tinsley, 1974). Consequently, if viral-associated activity is attenuated by the lack of oxygen, the cells remain in a suspended or quiescent state.…”
Section: Resultsmentioning
confidence: 99%
“…Of the cell culture and infection parameters that influence BEVS, the cell density at time of infection (TOI) has the most significant effect on the ability of insect cells to support virus replication and subsequent recombinant protein production. Very early literature indicated that the effect manifested itself as a significant decrease in volumetric production of both wild-type virus and occlusion bodies at high cell density infection (Hink et al, 1977;Knudson and Tinsley, 1974;Stockdale and Gardiner, 1977;Vaughn, 1976;Wood et al, 1982). The same limitation, however, has been observed to afflict the recombinant baculovirus expressed proteins and virus (Caron et al, 1990;Lindsay and Betenbaugh, 1992;Radford et al, 1991Radford et al, , 1992Reuveny et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Methods have been developed for the gentle harvesting of insect cells using proteolytic enzymes. Because the replication and assay of NPV in cell culture is most efficient in low-density actively dividing cells [10][11][12][13] such harvesting methods can be of great use in studies on these viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Because the replication of NPVs is best in actively dividing low-density cell monolayers [10][11][12][13], the quality of cells used for preparing such cultures is very important. The development of gentle methods using proteolytic enzymes for harvesting insect cells, analogous to those used with vertebrate cells [7], may therefore have considerable advantages for studying NPV replication in vitro.…”
Section: Introductionmentioning
confidence: 99%